ChemInform Abstract: Cs7Sm11[TeO3]12Cl16 and Rb7Nd11[TeO3]12Br16, the New Tellurite Halides of the Tetragonal Rb6LiNd11[SeO3]12Cl16 Structure Type. Issue 1 (17th December 2015) - Charkin, Dmitri O.; Black, Cameron; Downie, Lewis J.; Sklovsky, Dmitry E.; Berdonosov, Peter S.; Olenev, Andrei V.; Zhou, Wuzong; Lightfoot, Philip; Dolgikh, Valery A.
Abstract: The new title compounds are prepared by a salt flux technique from mixtures of TeO2, LnOX (Ln: Sm, Nd; X: Cl, Br), and MX (M: Rb, Cs) in evacuated silica tubes (850 °C, 150 h, <80% yield).